Analysis of professional gender stereotypes of students specializing in economics - Shemyhon, N.; Pasychnyk, E. (Problems of Engineer-Pedagogical Education, 2019)
The existence of gender stereotypes in professional activity largely limits freedom and prospects of self-realization of an individual, with gender equality being one of the topical issues in Ukrainian society. The article presents an overview of basic professional gender stereotypes of Ukrainian society and their contents, analyzes professional gender stereotypes of students specializing in economics, and defines measures which can help overcome gender stereotypes in relation to profession activity of future economists. Bright influence of gender stereotypes on professional activity can be seen both in vertical (concentration of women and men on the certain levels of professional hierarchy) and in horizontal employment. Women in Ukraine continue to prevail in the subzero echelon of the career ladder and continue to be poorly presented in top management. The research conducted in Ukrainian Engineering Pedagogics Academy at the Faculty of Economics confirms, on the whole, a general tendency about the presence of the preconceived ideas about masculinity and femininity of certain professions. As a result of the analysis it was discovered that both men and women tend to form stereotypical value judgments in relation to people of different sexes.